USE OF PIPE FINDERS IN SEARCHING OF UNDERGROUND PIPELINES IN GEODETIC MEASUREMENTS - Docent Juraeva Husnora Davronovna; Karshibaev Ilhom (Journals Park Publishing, 2024)
This article shows how important pipe finders are in surveying and construction in general today. The article describes the importance of pipe finders and how accurately measurements can be carried out. In addition, there are various instructions on how to prepare and use pipe finders. Various safety rules are explained in order to prevent possible problems. Most importantly, information is given about the necessity of this equipment in the field of geodesy. Some information about what to pay attention to when using a pipe finder and how to use a pipe finder is given.
Keywords: transmitter, generator, electromagnetic field, electromagnetic signal, electromagnetic induction, frequencies, GPS system, signal microprocessor, induction current, decibel(dB), milliAmpere(mA), marker, topographic plan, closed circuit, plastic pipes, LCD display.